Vico’s New Science: on mathesis universalis and heroic language - Vitiello, Vicenzo (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
Against the traditional interpretation of Vico as an anticartesian philosopher of civil society’s history, the first part of this essay depicts the New Science as an extension to the historical world of the mathesis universalis. This is proved by the axiomatic method present in the first Book(the so called Dignities) and by the division in three ages —of gods, of heroes and of men— of the necessary historical order: Vico’s «eternal ideal history», above which the nations’ histories «pass by within time». The second part of the article deals with the «heroic language» and shows the limitations of this mathesis, unable to express —as Vico itself admits— through an abstract and reflexive language the first age of the world: the arousal from nature’s ingens sylva of the historical human kind. In this way, Vico restores history and historiography with all their problematic complexity.
Keywords: Truth; language; body; gesture; ideal history; temporal history